2017
DOI: 10.5296/jss.v3i1.11104
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Safety and Health Conditions and Facilities in Small Industries in Jeddah, Saudi Arabia

Abstract: A lot of attention has been paid to improving occupational safety and health (OSH) in small scale industries all over the globe. This study describes the outcomes of a preliminary OSH status assessment in small scale industries of motor vehicle repair workshops (MVRW) in Jeddah, Kingdom of Saudi Arabia (KSA). An inspection tool composed of 10 OSH elements and 62 items employed walk-through survey, observations and interviews. The mean positive responses for different OSH elements surveyed were as follows; pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…Also, the association between level of education and use of protective measure revealed that low-level education is a contributory factor to non-use of protective equipment among vulcanizers in the study area. This finding supported previous findings that finding that low education level may contribute to non-use personal protective measures among small scale business workers, as they do not know, recognize and appreciate the significance of personal protective equipment (Ahmad et al, 2017;Kumar et al, 2013;Abraham et al, 2015;Taha 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Also, the association between level of education and use of protective measure revealed that low-level education is a contributory factor to non-use of protective equipment among vulcanizers in the study area. This finding supported previous findings that finding that low education level may contribute to non-use personal protective measures among small scale business workers, as they do not know, recognize and appreciate the significance of personal protective equipment (Ahmad et al, 2017;Kumar et al, 2013;Abraham et al, 2015;Taha 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Small-scale industries account for a large proportion of jobs and play a very vital role in most countries’ economic growth and prosperity, but in many cases the jobs are low-paid and the job security is poor (Ahmad et al, 2017). According to Webster's New World Finance and Investment Dictionary (2010), a privately-owned and operated business/activity with relatively small turnover and staff numbers is termed as the small industry.…”
Section: Introductionmentioning
confidence: 99%
“…The small-scale industry can also be defined as non-manufacturing industries employing less than 20 employees and manufacturing industries with less than 100 employees (Seneviratne and Phoon 2006). The main characteristics of the small-scale industries include; operated and owned independently, closely controlled by managers/owners who contribute to the operating capital and are the principal decision makers (Ahmad et al, 2017). There is a dearth of actual and reliable data available to the public on the number of workers in informal small repair workshops in the Kingdom of Saudi Arabia (KSA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations